Keanekaragaman Tumbuhan Bawah dan Manfaatnya di Gunung Cakrabuana, Majalengka - Yayan Hendrayana; Ibnu Fajar Sistiadi; Nurdin Nurdin; Ai Nurlaila; Ilham Adhya (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2022)
Understorey is a sub-stratification community near the soil surface which has the function of being able to prevent soil erosion, keep water from entering the soil and resist surface runoff so that it plays a role in increasing soil organic matter. The purpose of this study was to determine the diversity of understorey plants and their benefits found on Mount Cakrabuana Petak 10A RPH Lemahsugih BKPH Talaga KPH Majalengka. The method used is a grid line measuring 1 m x 1 m with a total of 44 sample plots. All plant species included in the plot were counted and identified. There are 48 types of understorey plants from 33 families that have a high diversity index (3.27) and have benefits as understorey plants that have the potential as ornamental plants and medicinal plants. This information is very important especially for the management of protected areas bordering the community